BRCA1/BRCA2 Germline Gene Mutations in Breast Cancer Egyptian Female Patients - Elsayed, Sally; Talkhan, Hala Ahmed; Mamdouh, Rasha; Sabry Elkady, Mohamed; Elkabarity, Rania Hamdy; Wahba, Nancy Samir (QJM : An International Journal of Medicine, 2024)
Breast cancer (BC) is the most commonly diagnosed cancer and the leading cause of cancer related deaths among women worldwide. Deleterious germline mutations in BRCA1 and BRCA2 genes underlie a major proportion of the inherited predisposition to BC and may lead to more aggressive disease. However, in many developing countries, including Egypt, knowledge of the prevalence of BRCA1/2 mutations among women with BC is sparse. The aim of the current study was to evaluate the contribution of germline mutations in BRCA1/2 to BC among Egyptian female patients. A case control study was conducted and included 30 Egyptian adult females diagnosed with BC, and 20 age matched Egyptian healthy females as control group. Real time polymerase chain reaction (PCR) was used for detection and allelic discrimination of BRCA1 mutations (185delAG, 4153delA, 5382insC, 3819delGTAAA, 3875delGTCT, 300T>G, 2080delA) and BRCA2 mutation (6174delT) in all included subjects. None of the studied mutations of the BRCA1 and BRCA2 genes were detected in BC patients or in the healthy control group included in the study. Key words: Breast cancer, BRCA1, BRCA2, gene mutation, prevalence.